Petr Rychkov’s Map of Iske (Inner or Old) Kazan of 4 July 1770 - Boterbloem K; Khabibullin A.; Fakhrullin R. (Золотоордынское обозрение)
Research objectives: On the basis of a recently discovered map – found in the manuscript library of the Russian Academy of Sciences in St. Petersburg – of Iske Kazan’s fortification made by P.N. Rychkov in 1770, this article investigates the manner in which its population protected itself against its foes in the restless era that witnessed the dissolution of the Golden Horde and the transition to the Kazan khanate. It additionally asks why in fact this map was composed. Research materials: Combining the evidence of Rychkov’s map with archaeological findings and in dialogue with the relevant historiography, the authors place the map in its historical context and ponder its significance, and suggest why this map was made in 1770. Results and novelty of the research: It appears that Iske Kazan’s inhabitants turned to a unique manner to defend themselves against their enemies, using a wall-moat-wall design to prevent any storming by mounted troops, different from what has been hitherto thought about the ruins of this defensive structure. This manner of defending seems eminently well suited to the restless conditions prevailing in the Volga-Kama region around 1400 and the art of war as practiced in this region. The article additionally suggests why this map was made in 1770, linking it to the general desire of the Romanov government to discover much more precisely how its subjects lived their lives. This impetus was born from the introduction of the Western-European scientific mindset in Peter I’s reign, which paid much closer heed to a realistic understanding of nature and culture. The Russian Academy of Sciences mounted from the 1720s onward a host of scientific expeditions, which almost resemble voyages of discovery, to map the tsarist empire, of which Rychkov’s travels formed a part. The article hints at the possibility that such fact-finding missions gradually allowed the central government in St. Petersburg to increase its power over its subject peoples.